Reducing psychological distress in patients with inflammatory bowel disease by cognitive-behavioural treatment: exploratory study of effectiveness - Mussell, Monika; Böcker, Ulrich; Nagel, Nils; Olbrich, R.; Singer, Manfred V. (Scandinavian journal of gastroenterology, 2003)
Background: This prospective study aimed to determine whether cognitive-behavioural group treatment accompanying medical standard care is effective in reducing psychological distress in patients with inflammatory bowel disease. Methods: Twenty-eight outpatients with Crohn disease or ulcerative colitis completed the treatment programme. Psychological treatment consisting of 12 weekly sessions was conducted in a group setting. Medical and psychometric assessments were taken at the beginning of the 3-month pretreatment waiting period, at pretreatment, at post-treatment and at the 3, 6 and 9-month follow-ups. Results: During baseline, no change was observed in psychological distress. Disease-related worries and concerns decreased significantly from pretreatment to the follow-ups. The disease groups differed in the decline of concerns between pre- and post-treatment, with a significant reduction of concerns in patients with ulcerative colitis but not Crohn disease. This difference did not occur at the follow-ups, indicating long-term improvement for both disease groups. Depressive coping decreased significantly in women and remained stable at the follow-ups, whereas depressive coping did not change in men. The same gender difference was found for depressive symptoms. Conclusions: The exploratory findings suggest that psychological group treatment for outpatients is a feasible and effective approach for the short- and long-term reduction of psychological distress for patients with inflammatory bowel disease. However, the revealed gender differences on coping and depression might indicate the necessity to consider gender-specific aspects of inflammatory bowel disease when designing and evaluating psychological interventions.